2022
DOI: 10.3390/ijms23031817
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress Resistance Mechanisms of Two Cucumber Varieties from Different Regions

Abstract: High temperatures affect the yield and quality of vegetable crops. Unlike thermosensitive plants, thermotolerant plants have excellent systems for withstanding heat stress. This study evaluated various heat resistance indexes of the thermotolerant cucumber (TT) and thermosensitive cucumber (TS) plants at the seedling stage. The similarities and differences between the regulatory genes were assessed through transcriptome analysis to understand the mechanisms for heat stress resistance in cucumber. The TT plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 101 publications
0
35
0
1
Order By: Relevance
“…JrGRAS2 in turn regulates the expression of heat shock proteins and thereby improves high temperature stress tolerance (Yang et al, 2018). In a recent transcriptomics study in cucumber, DOF transcription factor was found to be upregulated (Yu et al, 2022). A transcriptomic and proteomic analysis would be conducted to understand the candidate molecular targets of OsDOF27, which will allow us to get deeper insight and delineate the detailed molecular mechanisms of heat stress tolerance imparted by DOF27 in rice.…”
Section: Discussionmentioning
confidence: 99%
“…JrGRAS2 in turn regulates the expression of heat shock proteins and thereby improves high temperature stress tolerance (Yang et al, 2018). In a recent transcriptomics study in cucumber, DOF transcription factor was found to be upregulated (Yu et al, 2022). A transcriptomic and proteomic analysis would be conducted to understand the candidate molecular targets of OsDOF27, which will allow us to get deeper insight and delineate the detailed molecular mechanisms of heat stress tolerance imparted by DOF27 in rice.…”
Section: Discussionmentioning
confidence: 99%
“…The daily stress period could have drastically decreased the A CO2 and gs, as cucumber plants are a thermophilic crop that grows optimally at 25 • C [30], but temperatures above 35-50 • C can lead to leaf damage and even dead tissue [31]. Under these conditions, it has been reported that both thermo-tolerant and thermo-sensitive cucumber species show decreased leaf gas exchange parameters, but only thermo-tolerant cucumber species restore functions to a relatively healthy level after high-temperature exposure [32]. Nevertheless, A CO2 and g s reduction in treated plants could be due to an adaption mechanism to high light and temperature favoured by Archer ® Eclipse's application, since leaf damage was not observed and Fv/Fm, PIABS, RC/ABS, and ΨEO values were higher than in non-treated plants [15].…”
Section: Discussionmentioning
confidence: 99%
“…The maximum photochemical efficiency of PSII (Fv/Fm) was measured with an IMAGING-PAM chlorophyll fluorescence system (Heinz Walz GmbH, Effeltrich, Germany) using default parameters according to Yu’s [ 25 ]. After tea leaves adapted to the dark for 20 min, Fo was measured.…”
Section: Methodsmentioning
confidence: 99%